ENVIRONMENTAL PROTECTION THROUGH ENVIRONMENTAL SERVICES PAYMENTS - Silva, Viviane Farias; Lima, Wanessa Regina Geraldo; Bezerra, Carlos Vailan Castro; Lima, Vera Lucia Antunes; Baracuhy, José Geraldo Vasconcelos (Ciência e Natura, 2017)
To provide goods and services to human’s ecosystems need water like fish, timber, food, grains, among others. Similarly, are responsible for important services for the preservation of the quality and quantity of water available, such as the supply and maintenance of water flows and smoothing of natural disasters related to water, such as floods and droughts. This work was carried out to explain why the existence of this type of payment services in the pursuit of environmental protection exercised in several countries including environmental Brazil, based on the location of cases of payment for environmental services. Some countries have already practiced the payment for environmental services and the majority of services is related to water. Environmental service providers whose main goal that the business is profitable and remains. Payment for environmental service exists as an incentive to conserve the environment so profitable to the owner of rural land or forests ale smallholders and farmers.